What Are Agriculture Industry Professionals Trying to Tell Us? Implications for University-Level Agricultural Communications Curricula - David L. Doerfert; René P. Miller (Journal of Applied Communications, 2006)
Two recent activities have solicited the input of professionals on the future of agricultural communications within the agriculture industry. This paper reexamines these industry-based information and research activities for potential themes that could impact the current and future direction of communications-related activities within the agriculture profession. A reexamination of the outcomes of these two activities may provide insight and guidance for curricular and degree changes being considered by university-level agricultural communications educators. The four themes identified and discussed in this article are as follows: (a) the rapidly changing communication needs, wants, and expectations of the agriculture industry; (b) the new stakeholders of agricultural communications activities and products, and their diverse communication needs, wants, and preferences; (c) the shortened response time for communication-related activities; and (d) the increasing importance of the image of the agriculture industry and agricultural communications professionals. The themes that have emerged from industry through this study underscore the importance of researching the employee needs of the 21st century agriculturalist and agricultural communicator. These results may also positively influence university-level curricula and degree programs both within and outside of agricultural communications.